Pensar la imagen - Calvo-Gens, Laura (Arte, Individuo y Sociedad, 2022)
Reseña de la obra de Alloa, E. (Ed.) (2020). Pensar la imagen. Santiago de Chile, Metales Pesados, 250 pp., ISBN: 978-956-6048-22-0